2018
DOI: 10.3389/fphar.2018.00055
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis Is an Inflammatory Disease which Lacks a Common Anti-inflammatory Therapy: How Human Genetics Can Help to This Issue. A Narrative Review

Abstract: Atherosclerosis is a multifactorial disease triggered and sustained by different risk factors such as dyslipidemia, arterial hypertension, diabetes mellitus, smoke, etc. Since a couple of decades, a pivotal role for inflammation in its pathogenesis has been recognized and proved at molecular levels, and already described in many animal models. Despite all this knowledge, due to the complexity of the specific inflammatory process subtending atherosclerosis and to the fact that inflammation is also a protective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 63 publications
0
50
0
4
Order By: Relevance
“…Five patients with VTE and 3 patients without VTE had a history of CAD; MIAT was upregulated only in patients with VTE, suggesting that MIAT may be specific for VTE in our cohort, although confirmation is necessary. Additionally, recent studies have identified gene expression profiles in patients with atherosclerosis that do not possess MIAT . Similarly, NLRP14 is a member of NLRP3 genes responsible for activation of the inflammasome complex, which may be associated with thrombotic events .…”
Section: Resultsmentioning
confidence: 99%
“…Five patients with VTE and 3 patients without VTE had a history of CAD; MIAT was upregulated only in patients with VTE, suggesting that MIAT may be specific for VTE in our cohort, although confirmation is necessary. Additionally, recent studies have identified gene expression profiles in patients with atherosclerosis that do not possess MIAT . Similarly, NLRP14 is a member of NLRP3 genes responsible for activation of the inflammasome complex, which may be associated with thrombotic events .…”
Section: Resultsmentioning
confidence: 99%
“…Thus far, we have validated significant KO‐specific increases in expression for 10 genes identified by NanoString analysis (Figure 5B,C), most of which have been previously shown to have proven roles in the pathogenesis of atherosclerosis. These include (i) von Willebrand factor (VWF), an endothelial‐associated factor that facilitates platelet interactions and early atherogenesis 64 ; (ii) Lipocalin (LCN) 2, which promotes polarization and migration of plaque macrophages 65 ; (iii) Endoglin, an endothelial and SMC protein with a positive role in the pathogenesis of atherosclerosis 66 ; (iv) S100a8, a protein that is expressed by inflammatory macrophages and promotes atherosclerosis 67 ; (v) CCL2 (monocyte chemoattractant protein‐1), a chemokine with a fundamental role in monocyte recruitment in the subendothelium (an early event in atherosclerosis) 68,69 ; and (vi‐vii) CXCL12 70 and Pecam1, 71 which are both endothelium cell‐derived factors known to promote atherosclerosis and to be strongly associated with coronary artery diseases as shown by the presence of several SNPs in patients from multiple populations 72 . It is important to note that the GAIT element‐mediated atheroprotective mechanism that we have identified relies on L13a‐dependent translational silencing of target genes 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis is a chronic progressive inflammatory disease [1][2][3][4]. Atherosclerotic lesions are characterized by the accumulation of vascular smooth muscle cells (VSMCs) and extracellular matrix proteins, especially proteoglycan, collagen and elastin.…”
Section: Introductionmentioning
confidence: 99%